2020
DOI: 10.4236/ojfd.2020.103013
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Numerical Investigation of Airborne Droplet Dispersion in Aircraft Cabins

Abstract: The emergence of the novel coronavirus has led to a global pandemic which has led to the airline industry facing severe losses. For air travel to recover, airlines need to ensure safe air travel. In this paper, the authors have modeled droplet dispersion after a single breath from an index patient. Computational Fluid Dynamics (CFD) simulations are conducted using the k-ωSST turbulence model in ANSYS Fluent. The authors have taken into consideration several parameters such as the size of the mouth opening, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Long periods of travel make passengers and crew members more sensitive to the cabin environment [ 2 , 3 ]. The airborne transmission of infectious diseases has been reported in commercial aircraft, such as the transmission of influenza [ 4 ], tuberculosis [ 5 ], severe acute respiratory syndrome (SARS) [ 6 ], and coronavirus disease 2019 (COVID-19) [ [7] , [8] , [9] , [10] , [11] , [12] ]. Therefore, research on the indoor environments of airliner cabins is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Long periods of travel make passengers and crew members more sensitive to the cabin environment [ 2 , 3 ]. The airborne transmission of infectious diseases has been reported in commercial aircraft, such as the transmission of influenza [ 4 ], tuberculosis [ 5 ], severe acute respiratory syndrome (SARS) [ 6 ], and coronavirus disease 2019 (COVID-19) [ [7] , [8] , [9] , [10] , [11] , [12] ]. Therefore, research on the indoor environments of airliner cabins is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of COVID-19, scientists has focused most of their attention on the investigation of respiratory droplets produced by people who are infected by this virus. Bhatia and Santis [25] simulated dispersed droplets which are exhaled by a single breath of an index patient placed inside a 10 m 2 cabin area, using the k − ω ST turbulence model conducted in ANSYS Fluent to provide an insight into visualizing droplets. The results show that about 75% of droplets disperse within the cabin for up to 2 m axially behind the infected person by mixing with the airflow during 20 s. This exposes the passenger sitting behind the index patient to the risk of infection by dispersed droplets.…”
Section: Airborne Virus Dispersionmentioning
confidence: 99%
“…Since the COVID-19 outbreak, researchers have focused on the CFD-based investigations on SARS-CoV-2 transmission from affected individuals through droplets. Bhatia and De Santis [16] used the k-ωST turbulence model simulated using Ansys Fluent software to analyze the airborne SARS-CoV-2 dispersion in airplane cabins. e authors demonstrated a 75% chance of droplet transmission up to 2 m within the airplane cabin area.…”
Section: Introductionmentioning
confidence: 99%